Analysis and Strategy to Improve Student Satisfaction on Community Based Learning and Local Potential Methods - Ahmad Thoriq; In in Hanidah; Wahyu Gunawan (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2018)
One of the learning innovations developed by Padjadjaran University is a community-based learning method and local potential applied to arts and entrepreneurship courses (OKK). In order to improve the quality of academic services in the learning process it is necessary to analyze student satisfaction. The research design used in this study was a cross sectional study with a total sample of 133 first-degree students selected using the convenience sampling method. Data on satisfaction and expectations were collected through questionnaires and processed using the Importance Performance Analysis (IPA) and Custumer Satisfaction Index (CSI) which were then analyzed descriptively. Based on the results of the IPA analysis, the attributes that enter into quadrant I (top priority) are improvement in creativity and thinking patterns (c2) and understanding of culture, art, and local sports (c6), quadrant II (maintaining achievement), that is caring (c4 ) and the increase in soft skills (c7), quadrant III (low priority), namely the effectiveness of implementation (c1) and the spirit of entrepreneurship (c5), quadrant IV (excessive), namely teamwork (c3). Overall student satisfaction with the seven attributes that affected the implementation of OKK lectures was 74.20%.